A call for action: Educating pharmacists and pharmacy students in behaviour change techniques - Caitlin Liddelow; Barbara A. Mullan; Hayley Breare; Tin Fei Sim; Darren Haywood (Elsevier, 2023)
The increasing impact of chronic disease, including cancer and heart disease on mortality signifies a need for the upskilling of health professionals in health behaviour change. Solely providing education and information to patients is generally not sufficient to change behaviour, and for any change to be sustained. The nature of pharmaceutical practice allows pharmacists to have frequent contact with patients in the community. Historically, pharmacists have often effectively engaged with patients to assist with behaviour change initiatives related to smoking cessation, weight loss or medication adherence. Unfortunately, such initiatives do not work for everyone, and more tailored and varied interventions are urgently needed to reduce the effects of chronic disease. In addition, with greater inaccessibility to hospitals and GP's (e.g., appointment wait times), it is imperative that pharmacists are upskilled in providing opportunistic health behaviour change techniques and interventions. Pharmacists need to practice to their full scope consistently and confidently, including the use of behavioural interventions. The following commentary therefore describes and provides recommendations for the upskilling of pharmacists and pharmacy students in opportunistic behaviour change. We outline nine key evidence-based behaviour change techniques, the active-ingredients of a behaviour change intervention, that are relevant to common encounters in professional practice by pharmacists, such as improving adherence to medications/treatments and health promotion initiatives. These include social support (practical and emotional), problem solving, anticipated regret, habit formation, behaviour substitution, restructuring the environment, information about others' approval, pros and cons, and monitoring and providing feedback on behaviour. Recommendations are then provided for how this upskilling can be taught to pharmacists and pharmacy students, as well as how they can use these techniques in their everyday practice.